2009
DOI: 10.1016/j.automatica.2009.04.013
|View full text |Cite
|
Sign up to set email alerts
|

On linear co-positive Lyapunov functions for sets of linear positive systems

Abstract: In this paper we derive necessary and sufficient conditions for the existence of a common linear co-positive Lyapunov function for a finite set of linear positive systems. Both the state dependent and arbitrary switching cases are considered. Our results reveal an interesting characterisation of "linear" stability for the arbitrary switching case; namely, the existence of such a linear Lyapunov function can be related to the requirement that a number of extreme systems are Metzler and Hurwitz stable. Examples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
91
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(92 citation statements)
references
References 18 publications
1
91
0
Order By: Relevance
“…Definition 6: Given positive switched delta operator system (1), for two positive scalars γ and β, the observer (5) is said to be an l -/l 1 fault detection observer if 1) Error system (6) is exponentially stable when ( ) 0 w k = and ( ) 0; f k = 2) Under zero initial conditions, (9) and (10) hold.…”
Section: Problem Formulation and Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Definition 6: Given positive switched delta operator system (1), for two positive scalars γ and β, the observer (5) is said to be an l -/l 1 fault detection observer if 1) Error system (6) is exponentially stable when ( ) 0 w k = and ( ) 0; f k = 2) Under zero initial conditions, (9) and (10) hold.…”
Section: Problem Formulation and Preliminariesmentioning
confidence: 99%
“…It should be pointed out that a linear co-positive Lyapunov functional is powerful for the analysis and synthesis of positive systems [7]. Some results on the stability and stabilization of such systems have been obtained in [8,9]. It has been shown that the l 1 performance index can characterize effectively the disturbance attenuation performance because of the peculiar nonnegative property of positive systems [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the existence of CLCLFs implies asymptotic stability of PSLSs under arbitrary switching. Moreover, necessary and sufficient conditions for the existence of CLCLFs have been extensively investigated in [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, positive switched systems have been highlighted and investigated by many researchers due to the broad applications in communication systems [30,31], formation flying [11], the viral mutation dynamics under drug treatment [21] and systems theories [1,13,14,27,28]. However, it should be pointed out that to obtain some results on positive switched systems, one has to combine both features of general switched systems and positive systems [3,4,6,15,16,22,26].…”
Section: Introductionmentioning
confidence: 99%